The Politics of Syrian Refugees in Turkey: A Question of Inclusion and Exclusion through Citizenship - Akçapar, Şebnem Köşer (Social Inclusion, 2018)
Turkey began to receive refugees from Syria in 2011 and has since become the country hosting the highest number of refugees, with more than 3.5 million Syrians and half a million people of other nationalities, mainly from Afghanistan, Iraq and Iran. An important turning point regarding the legal status of Syrian refugees has come with recent amendments to the Turkish citizenship law. Based on ongoing academic debates on integration and citizenship, this article will explore these two concepts in the case of Syrian refugees in Turkey. We will argue that the shift in the Turkish citizenship law is a direct outcome of recent migration flows. We further argue that the citizenship option is used both as a reward for skilled migrants with economic and cultural capital and as a tool to integrate the rest of the Syrians. It also reflects other social, political and demographic concerns of the Turkish government. Using our recent ethnographic study with Syrians and local populations in two main refugee hosting cities in Turkey, Istanbul and Gaziantep, we will locate the successes and weaknesses of this strategy by exemplifying the views of Syrian refugees on gaining Turkish citizenship and the reactions of Turkish nationals.